Baby Calf - Hinds, P. Mignon; Needham, James M. (New York : Golden Book ; Racine Wisc. : Western Pub. Co., 1988)
The simple adventures of a baby calf.
"A golden book."
Keywords: Cows -- Juvenile literature; Animals -- Infancy -- Juvenile literature